2007
DOI: 10.1507/endocrj.k07-059
|View full text |Cite
|
Sign up to set email alerts
|

Defective Expression of Prohormone Convertase 1/3 in Silent Corticotroph Adenoma

Abstract: Abstract. Silent corticotroph adenoma (SCA) is defined as an ACTH-producing pituitary tumor not associated with clinical and endocrine feartures of Cushing's syndrome, but its underlying molecular mechanism(s) remains unknown thus far. We tested the hypothesis that reduced expression of prohormone convertase (PC) 1/3 responsible for proteolytic processing of proopiomelanocortin (POMC) in SCA may lead to production of unprocessed, biologically inactive POMC and/or precursor of ACTH. Among 30 non-functioning pit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 19 publications
0
30
0
1
Order By: Relevance
“…Immunohistochemical and RT-PCR studies have already demonstrated a decrease in PC1/3 expression in SCAs than in corticotroph adenomas (26,27) or non-functioning pituitary adenomas (7,26,27). However, in these rare studies, few SCAs were analyzed, the hormonal data at presentation were sparse, and no distinction was made between micro-or macro-ACTH tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical and RT-PCR studies have already demonstrated a decrease in PC1/3 expression in SCAs than in corticotroph adenomas (26,27) or non-functioning pituitary adenomas (7,26,27). However, in these rare studies, few SCAs were analyzed, the hormonal data at presentation were sparse, and no distinction was made between micro-or macro-ACTH tumours.…”
Section: Discussionmentioning
confidence: 99%
“…SCAs potentially derive from POMC producing cells in the vestigial pars intermedia of the human pituitary [17], and the clinical silence may be due to dysregulated POMC processing [37]. Prohormone convertase (PC) 1/3 transcripts, which cleave POMC to ACTH, indeed are downregulated in SCAs [51], with CD having 30-fold higher levels than SCAs, and 10-fold higher levels observed in type I compared to type II SCAs which further suggest a defect in conversion of POMC to ACTH in SCAs [20].…”
Section: Pathogenesismentioning
confidence: 99%
“…Interestingly, a family with FIPA harbouring subtype 2 silent corticotroph adenoma has recently been described [6]. The silent corticotroph adenoma subgroup members (subtypes 1 and 2) seem to have a more aggressive clinical course and higher recurrence rate than null cell adenomas and oncocytomas [13,14,15]. Corticotroph carcinoma presenting as a silent corticotroph adenoma has also been described [16].…”
Section: Silent Pituitary Adenomasmentioning
confidence: 99%
“…Several studies suggest that this last mechanism, related to reduced prohormone convertase, could play a role [14, 26], but it has not been uniformly found. Other genes were also differentially expressed in silent corticotropinomas compared with corticotroph adenomas, such as NeuroD1 , CRHR , V1bR and 11 β -HSD2 [27].…”
Section: Why Are Silent Corticotroph Adenomas Silent?mentioning
confidence: 99%